Foreword to the publication: Friedrich Weisman "What is logical analysis?" (Actual Problems of Mind, 2017)
Foreword to the publication: Friedrich Weisman "What is logical analysis?"
Keywords: Vienna Circle; Logical Positivism; Friedrich Weisman; logical analysis